2000
DOI: 10.1046/j.1440-1819.2000.00682.x
|View full text |Cite
|
Sign up to set email alerts
|

The survey of sleeping time of junior high school students: A study on the sleep questionnaire

Abstract: We investigated the questionnaire study on sleep of junior high school students to estimate the effect of excessive study hours on their sleep time in 1998. A total of 501 students answered the questionnaire. It was noted that most of the students sleep for 6-8 h on weekdays. The majority of the students of the junior high school felt that their sleep is insufficient on weekdays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Comparison of these data with those in other sleep studies revealed that Taiwanese adolescents slept as little as, or less than, those in other countries. For example, Yamaguchi et al [ 22 ] reported that most junior high adolescents in Japan received 6–8 hours of sleep on weekdays. Masalan et al [ 23 ] found that 44.2% of high school adolescents in Chile had sleeping disorders that were associated with environmental conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of these data with those in other sleep studies revealed that Taiwanese adolescents slept as little as, or less than, those in other countries. For example, Yamaguchi et al [ 22 ] reported that most junior high adolescents in Japan received 6–8 hours of sleep on weekdays. Masalan et al [ 23 ] found that 44.2% of high school adolescents in Chile had sleeping disorders that were associated with environmental conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 Due to the practical and economical aspects, self-reported sleeping habit questionnaires remain to be the most requested and widely used method. 3 , 4 Subjective sleep assessments, in our study daily sleep diaries, are agreeable for participants, require minimum supervision and can be easily completed. Objective methods, like actigraphy, provide accurate information on the sleep-wake patterns.…”
mentioning
confidence: 99%